D. Leopoldina Habsburg-Lothringen: uma revisão historiográfica na construção do Brasil como Estado-Nação - Francisco, Daniele dos Santos (Universidade Federal de São Carlos, 2025)
This research focuses on the contributions of Dona Leopoldina Habsburg-Lothringen to the construction of Brazil as a nation-state, using the analytical categories of politics, socio-educational development, and culture. The research focuses on the actions and influence of the first Empress of Brazil in the processes of formation and consolidation of the country as an independent and sovereign nation. The research problem lies within these contributions to the construction of the Brazilian nation. The timeframe is limited to the first decades of the 19th century. The methodology employed is a systematic literature review of the meta-synthesis type and historiography from the epistemological perspective of Cultural History. The historiographical review intersects with the analytical category of gender to better investigate the gender relations, patriarchy, and coloniality that permeated the ideology and social relations of the time and that still reverberate. This intersection corroborates the understanding of the historiographical erasure that this historical figure suffered throughout the construction of Brazilian history, a history that was and still is widely taught in schools. To achieve the research objectives, classic works, biographies, and academic texts from the 19th, 20th, and 21st centuries were analyzed. The research is centered on the fields of science, history, and education. The historiographical review of classic works on Brazilian history, encompassing the beginning of their production to the present, confirmed the research hypothesis that Dona Leopoldina suffered historiographical erasure regarding her contributions to the construction of Brazil as a nation-state, with her image being more recently established in academic productions and biographies within the process of the formation of the Brazilian nation. It is concluded that Dona Leopoldina suffered a deliberate historiographical erasure in the construction of Brazil as a nation-state in political, socio-educational, and cultural aspects. This portrait is clarified through the systematization of revised classic works under analytical categories, which gives little evidence of their contributions to the construction of Brazil as a nation-state in political, socio-educational, and cultural aspects. I emphasize that, in contrast, more recent academic productions and Paulo Rezzutti's 2017 biography have done justice to these contributions, including those prior to Brazil's political and administrative emancipation. His contributions are substantial and deserve a prominent place in Brazilian history.

Diese Forschungsarbeit untersucht den Beitrag von Kaiserin Leopoldina von Habsburg-Lothringen zur Entstehung Brasiliens als Nationalstaat. Dabei werden die analytischen Kategorien Politik, sozio-pädagogische Entwicklung und Kultur herangezogen. Im Fokus stehen das Wirken und der Einfluss der ersten Kaiserin Brasiliens auf die Prozesse der Formung und Festigung des Landes als unabhängige und souveräne Nation. Die Forschungsfrage liegt in diesem Beitrag zur Konstruktion der brasilianischen Nation. Der zeitliche Rahmen beschränkt sich auf die ersten Jahrzehnte des 19. Jahrhunderts. Die angewandte Methodik umfasst eine systematische Literaturanalyse im Sinne einer Meta-Synthese sowie eine Historiographie aus der erkenntnistheoretischen Perspektive der Kulturgeschichte. Die historiographische Analyse verknüpft sich mit der analytischen Kategorie Gender, um die Geschlechterverhältnisse, das Patriarchat und die Kolonialität, die die Ideologie und die sozialen Beziehungen jener Zeit prägten und bis heute nachwirken, genauer zu untersuchen. Diese Schnittmenge untermauert das Verständnis der historiografischen Auslöschung, die diese historische Persönlichkeit im Zuge der Konstruktion der brasilianischen Geschichte erlitt – einer Geschichte, die in Schulen weit verbreitet war und ist. Zur Erreichung der Forschungsziele wurden klassische Werke, Biografien und wissenschaftliche Texte des 19., 20. und 21. Jahrhunderts analysiert. Die Forschung konzentriert sich auf die Bereiche Wissenschaft, Geschichte und Bildung. Die historiografische Analyse klassischer Werke zur brasilianischen Geschichte, die deren Entstehung bis in die Gegenwart umfasst, bestätigte die Forschungshypothese, dass Dona Leopoldina hinsichtlich ihrer Beiträge zur Entstehung Brasiliens als Nationalstaat historiografischer Auslöschung ausgesetzt war und ihr Bild erst in jüngerer Zeit im Kontext des brasilianischen Nationsbildungsprozesses in wissenschaftlichen Publikationen und Biografien etabliert wurde. Es lässt sich feststellen, dass Dona Leopoldina bei der Entwicklung Brasiliens als Nationalstaat in politischer, sozio-pädagogischer und kultureller Hinsicht bewusst aus der Geschichtsschreibung ausgeblendet wurde. Diese Darstellung wird durch die Systematisierung klassischer Werke verdeutlicht, die anhand analytischer Kategorien untersucht wurden und nur wenige Belege für ihre Beiträge zur Entwicklung Brasiliens als Nationalstaat in diesen Bereichen liefern. Im Gegensatz dazu würdigen neuere wissenschaftliche Publikationen und ihre Biografie von Paulo Rezzutti aus dem Jahr 2017 diese Beiträge, einschließlich jener, die vor dem Prozess der politischen und administrativen Emanzipation Brasiliens entstanden sind. Ihre Beiträge sind substanziell und verdienen einen prominenten Platz in der Geschichte Brasiliens.
D. Leopoldina Habsburg-Lothringen: a historiographical review in the construction of Brazil as a nation-state.
D. Leopoldina Habsburg-Lothringen: eine historiographische Betrachtung zur Entstehung Brasiliens als Nationalstaat.
Keywords: Leopoldina; História do Brasil; Historiografia; História da Educação; History of Brazil; Historiography; History of Education; Geschichte Brasiliens; Geschichtsschreibung; Geschichte der Erziehung; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade